A Study on Phytochemical Screening and Analysis of Leaf Extract of Withania Somnifera - Fathaunnisha, S.; Hemamalini, V.; Jayasudha, H.; Sridhar, R. (International Journal of Scientific Research in Biological Sciences, 2020)
Withania somnifera is a highly renowned plant in the Indian Ayurvedic and Unani System of medicine. This plant is known to promote physical and mental health and is used to treat almost all of the disorders that affect human health. So, it is called as’ Power Herb’. The present study investigated the qualitative and quantitative phytochemical analysis of W. somnifera. The leaves were shade dried and powdered and sequentially extracted with Hexane, Ethyl acetate, and Ethanol solvents. Qualitative and Quantitative Phytochemical analysis was performed for the three extracts. The phytochemical analysis showed the presence of carbohydrates, tannins, saponins, flavonoids, alkaloids, quinones, phenols, etc., Quantitative estimation of the phytochemicals was also evaluated. Biologically active phytochemicals were mainly present in the Ethyl acetate extract of W. somnifera.